Laser-Induced Low-Resistance Ohmic Contacts on n-Si - Ismail, Raid A.; Hubeatir, Kadhim A.; Kalif, Nihaya H. (Iraqi Journal of Laser, 2006)
In the present work, the feasibility of formation near-ideal ohmic behavior of In/n-Si contact efficiently by 300 s duration Nd:YAG pulsed laser processing has been recognized. Several laser pulses energy densities have been used, and the optimal energy density that gives best results is obtained. Topography of the irradiated region was extensively discussed and supported with micrographic illustrations to determine the surface condition that can play the important role in the ohmic contact quality. I-V characteristics in the forward and reverse bias and barrier height measurements have been studied for different irradiated samples to determine the laser energy density that gives best ohmic behavior. Comparing the current results with published results, it is found that these results are competitive and meet the standards of good ohmic contact, specific contact resistance of 1.9 x 10-4 .cm2 has been obtained at 21.1 J.cm-2 laser energy density, which is the lowest value ever reported for In/n-Si.